Synthesis of titanium dioxide nanorod arrays using a facile aqueous sol-gel route for ultraviolet photosensor applications - Mohd. Yusoff, Marmeezee; Mamat, Mohamad Hafiz; Mahmood, Mohamad Rusop (IntechOpen, 2017)
In this chapter, we review the state of the art of aqueous sol-gel route for ultraviolet (UV) photosensor applications based on the nanostructured TiO2. The performance of UV photosensor is associated with the high surface-to-volume ratio, porosity, surface defects, light trapping, and the intensity of the UV radiation. One-dimensional (1D) growth of TiO2 nanorod arrays (TNAs) offers an enhance charge carrier mobility to overcome the photocurrent loss due to the existence of multiple grain boundaries in granular-like and porous nanostructures. Photoelectrochemical cell (PEC)-based device structure is preferred in TNA-based UV photosensor due to its low cost, facile fabrication process, high contact area, low recombination of the excitonic charge carriers, high photocurrent gain, and fast response and recovery times. It also could work in applied bias mode, as well as in “self-powered” mode. Our study has introduced a new one-step method to deposit a thin film TNA on an FTO-coated glass substrate at low temperature and a rapid process using a facile glass container. The fabricated PEC-based UV photosensor using the deposited TNAs has successfully shown its potential in the application of UV photosensor.